CRIMINAL RESPONSIBILITY FOR FRAUD MONEY Rp 285.000.000 OF OVERSEAS TRAVEL DOCUMENT PROCESSING (VISA) (Case Study of Police Report Number: LP / 432 / IX / 2020 / SULUT / SPKT) - Barail, Deiser; Borman, M.Syahrul; Handayati, Nur; Subekti, Subekti (Gapenas Publisher, 2025)
The difficulty of finding work in the country encourages many Indonesian workers to work abroad. To be able to leave Indonesia and be accepted in the destination country, one must have a visa as an entry permit and travel permit. However, there are still many people who do not understand the administrative procedures for visa processing, so service bureaus have emerged that offer document processing services. These service bureaus require operational and service fees. However, there are many cases where service bureaus receive money but do not fulfill their obligations, resulting in disputes that lead to police reports. This research examines criminal liability in visa processing fraud cases, with a focus on Police Report Case Study Number: LP/432/IX/2020/SULUT/SPKT. In addition, this study also analyzes the legal consequences of criminal fraud in visa management. The research method used is normative legal research, which examines legal norms based on a statutory approach. The analysis is carried out normatively qualitative with inductive logic, using the method of interpretation and comparative legal construction. In criminal law, fault is an important element in determining criminal liability. The principle of “no punishment without fault” emphasizes that a person can only be convicted if proven guilty. The legal consequences of the crime of visa fraud are criminal sanctions in accordance with Article 378 of the Criminal Code, which stipulates a maximum imprisonment of four years for perpetrators of fraud.